2001
DOI: 10.1210/jcem.86.1.7124
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Etiology to Treatment in Congenital Hypothyroidism

Abstract: We examined the patterns of TSH, T(4), and treatment schedules from diagnosis to 4 yr of age in 125 children (50 males anf 75 females) with congenital hypothyroidism (CH). Subjects were divided into 3 groups based on their thyroid scans: 1) athyreosis (n = 31), 2) dysgenesis (n = 54; 49 lingual and 5 hypoplastic), and 3) dyshormonogenesis (n = 40). Follow-up evaluation was carried out at 2-4 wk and 3, 6, 9, 12, 24, 36, and 48 months of age. Median gestational age, age at onset of therapy, and starting L-T(4) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(15 citation statements)
references
References 34 publications
1
13
0
1
Order By: Relevance
“…Our distribution of the different aetiologies of CH was comparable with previous studies (Grant et al ., 1992; Hanakoglu et al ., 2001; Hrytsiuk et al ., 2002). Although all our patients underwent Tc‐pertechnate radionuclide scans prior to treatment, not all patients had an ultrasound scan confirmed when an iodide uptake defect was detected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our distribution of the different aetiologies of CH was comparable with previous studies (Grant et al ., 1992; Hanakoglu et al ., 2001; Hrytsiuk et al ., 2002). Although all our patients underwent Tc‐pertechnate radionuclide scans prior to treatment, not all patients had an ultrasound scan confirmed when an iodide uptake defect was detected.…”
Section: Discussionmentioning
confidence: 99%
“…The use of radionuclide thyroid scans have enabled identification of aetiology of CH (Hanukoglu et al ., 2001; Song et al ., 2001). In studies where aetiology of CH was determined, those with athyreosis were found to have the least favourable outcome (Song et al ., 2001).…”
mentioning
confidence: 99%
“…Although in the management of hypothyroidism the plasma TSH concentration is considered a useful determinant, elevated plasma TSH concentrations are frequently encountered in the course of CH treatment (Working Group on Neonatal Screening of the ESPE, 1999; Fisher et al ., 2000; Hanukoglu et al ., 2001). To investigate which thyroid hormone determinants are most suitable to determine the achievement of euthyroidism, a retrospective analysis was made in a group of 30 CH patients with a well‐defined aetiology and in whom the plasma concentrations of TSH, free T4 (FT4), total T4 (T4) and total T3 (T3) had been measured frequently before and after initiation of T4 supplementation.…”
mentioning
confidence: 99%
“…[34] We found that in the first few years of life, children with athyreosis required more dose changes and closer monitoring than did those with the other etiologies, while children with ectopic glands showed elevated TSH values and needed dosage increases at both the end of the first and fourth years of life. [34] We found that in the first few years of life, children with athyreosis required more dose changes and closer monitoring than did those with the other etiologies, while children with ectopic glands showed elevated TSH values and needed dosage increases at both the end of the first and fourth years of life.…”
Section: Management Of Congenital Hypothyroidismmentioning
confidence: 67%